The Global boundary stratotype section and point (GSSP) for the base of the Albian Stage, of the Cretaceous, the Col de Pré-Guittard section, Arnayon, Drôme, France - J. M. Kennedy; A. S. Gale; B. T. Huber; M. R. Petrizzo; P. Bown; H. C. Jenkyns (Episodes, 2017)
Following the unanimous approval of the Executive Committee on the International Union of Geological Sciences as notified on April 8, 2016, the Global boundary Stratotype Section and Point for the base of the Albian Stage of the Cretaceous is defined at the first occurrence datum of the planktonic foraminiferan Microhedbergella renilaevis Huber and Leckie, 2011 at a level 37.4 meters above the base of the Marnes Bleues Formation and 40 cm above the base of the Niveau Kilian marker bed in the section SSE of the Col de Pré-Guittard, Arnayon, Drôme, France. The first occurrence of Microhedbergella renilaevis is placed within a 100-m section of argillaceous sediments with 28 secondary markers including calcareous nannofossils, planktonic foraminifera, an inoceramid bivalve, ammonites, stable carbon isotopes, and local marker beds.